Erratum: Pagonabarraga, J.; et al. A Spanish Consensus on the Use of Safinamide for Parkinson’s Disease in Clinical Practice. Brain Sci. 2020, 10, 176 - Javier Pagonabarraga; José Matías Arbelo; Francisco Grandas; Maria-Rosario Luquin; Pablo Martínez Martín; Maria Cruz Rodriguez-Oroz; Francesc Valldeoriola; Jaime Kulisevsky (Brain Sciences, 2020)
We would like to submit the following erratum to our recently published paper [...]